(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Current on-day education is the process of teachers’ new flexibility, which is the main factor that is spinning this article examines teachers’ new technologies and pedagogical approaches to acceptance of ability analysis. Modern education in the system of technological literacy, continuous the students’ qualification increase programs and creativity important profession Research shows that the news effective implementation to grow not only education quality increases, maybe students every one-sided to develop help give.